After the Death of Inflation: Will Fiscal Drag Survive? - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
Declining inflation rates might have negative consequences for tax revenues. Phenomena like the inflationary bracket creep in a progressive income tax system do not work any longer. With this background the paper analyzes the extent of fiscal drag for OECD countries since 1965. Some considerations on the role of money illusion and indexation in this context lay the theoretical base followed by a descriptive view on the relation between inflation, growth and tax revenues in the past decades. A framework is presented that allows for the classification of fiscal structures with regard to the type of fiscal drag. The subsequent econometric analysis is performed for total and disaggregated government revenues. The results reveal that an end of inflation would have a negative impact on tax revenues for a number of OECD countries. The results also back theoretical considerations on inflation?s impact on different kinds of taxes: This impact tends to be positive for individual income taxes and social security contributions, it is neutral or negative for corporate income, property and indirect taxation. The paper concludes that both declining inflation and recent trends in tax reforms can be expected to limit the potential for future fiscal drag.
Keywords: E63; H20; 330; bracket creep; fiscal drag; indexation; inflation; money illusion; Olivera-Tanzi effect; taxes; Wagner?s law; Steueraufkommen; Inflation; Wirtschaftswachstum; Geldillusion; Schätzung; Wagnersches Gesetz; OECD-Staaten